Domain Architecture of a Calcium-Permeable AMPA Receptor in a Ligand-Free Conformation - Midgett, Charles R.; Gill, Avinash; Madden, Dean R. (Frontiers in Molecular Neuroscience, 2012)
Ligand-gated ion channels couple the free energy of agonist binding to the gating of selective transmembrane ion pores, permitting cells to regulate ion flux in response to external chemical stimuli. However, the stereochemical mechanisms responsible for this coupling remain obscure. In the case of the ionotropic glutamate receptors (iGluRs), the modular nature of receptor subunits has facilitated structural analysis of the N-terminal domain (NTD), and of multiple conformations of the ligand-binding domain (LBD). Recently, the crystallographic structure of an antagonist-bound form of the receptor was determined. However, disulfide trapping of this conformation blocks channel opening, suggesting that channel activation involves additional quaternary packing arrangements. To explore the conformational space available to iGluR channels, we report here a second, clearly distinct domain architecture of homotetrameric, calcium-permeable AMPARs, determined by single-particle electron microscopy of untagged and fluorescently tagged constructs in a ligand-free state. It reveals a novel packing of NTD dimers, and a separation of LBD dimers across a central vestibule. In this arrangement, which reconciles diverse functional observations, agonist-induced cleft closure across LBD dimers can be converted into a twisting motion that provides a basis for receptor activation.